Eutectic gel coating modified zinc foil negative electrode, preparation method and application of eutectic gel coating modified zinc foil negative electrode
The zinc foil negative electrode is modified by a low eutectic gel coating, and the dendrite growth and hydrogen evolution reaction are suppressed by hydrogen bonding network, which improves the cycle stability and electrochemical performance of zinc ion batteries, solves the problem of poor cycle reversibility of zinc negative electrodes, and realizes the realization of More efficient battery performance and simple preparation process.
Patent Information
- Application Number
- CN202411328587.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
The zinc negative electrode cycle of zinc ion batteries is poor, mainly due to dendrite growth and hydrogen evolution reaction, which limits the development of zinc ion batteries.
The zinc foil negative electrode is modified by using a low eutectic gel coating. Through the combination of hydrogen bond donor and hydrogen bond acceptor, a polymerizable eutectic solvent of a ternary hydrogen bond network is formed, and polymerized under light conditions to form a gel coating. The layer improves the adhesion and mechanical properties of the zinc foil surface, and inhibits dendrites' growth and side reactions.
It significantly improves the cycle stability and Coulomb efficiency of zinc ion batteries, simplifies the preparation process, is suitable for large-scale production, reduces the interface impedance, and enhances electrochemical performance.
Smart Images

Figure HDA0005056136540000011 
Figure HDA0005056136540000012 
Figure HDA0005056136540000021
Abstract
Description
Technical Field
[0001] The invention relates to the field of battery materials, and in particular to a zinc foil negative electrode modified with a low eutectic gel coating, a preparation method and application thereof. Background Art
[0002] Zinc-ion batteries are safe, low-cost energy storage devices with great application potential in flexible and wearable devices. At present, zinc-ion batteries are mainly based on aqueous electrolytes. Due to the growth of dendrites on the zinc negative electrode, the occurrence of hydrogen evolution reaction, passivation and zinc corrosion, the cycle reversibility of the zinc foil negative electrode is poor, which greatly limits the development of zinc-ion batteries. How to improve the cycle reversibility of the zinc negative electrode is a major challenge currently faced.
[0003] There are currently four main methods for improving the cyclic reversibility of zinc foil negative electrodes: controlled synthesis; artificial surface coating; electrolyte additives and suitable separators. The artificial surface coating of zinc can directly physically isolate the electrolyte, inhibit the formation of zinc dendrites and the occurrence of side reactions. Although there are some methods for surface modification of zinc negative electrodes to improve performance, such as coating the surface of zinc foil with an organic layer, an inorganic layer or a composite coating. Polyaniline has good electrical conductivity and ion adsorption properties. For example, conductive polyaniline and high molecular polymer polyvinyl butyral ester are mixed and dissolved in an organic solvent such as N-methylpyrrolidone in a certain proportion, and then coated on the surface of zinc foil, and finally vacuum dried to obtain a composite organic coating modified zinc metal negative electrode (patent CN 116799192A). For another example, polyvinylidene fluoride-hexafluoropropylene copolymer and zinc salt are dissolved in an acetone solution, coated on the surface of zinc foil, and then vacuum dried to obtain a polymer coating modified zinc metal negative electrode (patent CN 114792775 A). The above two coatings can effectively inhibit the problems of zinc metal negative electrode dendrites and corrosion, but the preparation methods are complicated and require long-term vacuum drying, which may cause problems such as uneven coating shedding. Therefore, it is necessary to develop more efficient zinc foil coatings. Summary of the invention
[0004] The purpose of the present invention is to provide a zinc foil negative electrode modified with a low eutectic gel coating, a preparation method and its application. The coating is easy to prepare, has good adhesion to the zinc foil, high mechanical properties, low interface impedance, is conducive to inhibiting dendrite growth and side reactions, improving coulombic efficiency, and thus improving the electrochemical performance of the battery.
[0005] In order to achieve the above object, the present invention particularly adopts the following technical solutions:
[0006] The first aspect of the present invention provides a polymerizable low eutectic solvent for preparing a zinc foil negative electrode coating, wherein the preparation raw materials include: a hydrogen bond donor and a hydrogen bond acceptor, wherein the hydrogen bond donor contains an unsaturated double bond.
[0007] Preferably, the hydrogen bond donor is an acrylamide monomer and an alcohol. The introduction of alcohol can reconstruct a ternary hydrogen bond network with acrylamide and metal zinc salt. Compared with the binary hydrogen bond network composed of acrylamide / metal zinc salt, the ternary hydrogen bond network eutectic gel composed of acrylamide / metal zinc salt / alcohol has lower interface impedance and improved tensile properties.
[0008] Preferably, the acrylamide monomer is one or more of acrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide.
[0009] Preferably, the alcohol is a monohydric alcohol or a polyhydric alcohol.
[0010] Preferably, the hydrogen bond acceptor includes zinc tetrafluoroborate, zinc acetate, and zinc chloride.
[0011] Preferably, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 0.1:1 to 10:1.
[0012] The second aspect of the present invention provides a zinc foil negative electrode coating, comprising the following raw material components which are stored independently: the polymerizable low eutectic solvent described in the first aspect, and an initiator. The polymerizable low eutectic solvent and initiator.
[0013] Preferably, the initiator is a photoinitiator, including one or more of 2-oxoglutaric acid, 2-hydroxy-2-methyl-1-phenyl-1-propanone (PI1173), and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (PI2959).
[0014] The third aspect of the present invention provides a method for preparing the above-mentioned zinc foil negative electrode coating, comprising the following steps:
[0015] S1: mixing the hydrogen bond acceptor and the hydrogen bond donor in a certain molar ratio, heating and stirring until the mixture becomes clear and transparent, thereby obtaining a polymerizable low eutectic solvent;
[0016] S2: adding a small amount of initiator to the solution prepared in step S1 and mixing evenly to obtain a prepolymer solution;
[0017] S3: The prepolymer solution obtained in S2 is coated on a metal zinc foil, and then polymerized under light conditions to obtain a low eutectic gel coating.
[0018] Preferably, the polymerization condition of step S3 is polymerization under ultraviolet light conditions, and the ultraviolet curing reaction time is determined by the corresponding polymerization reaction and light power.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The low-melting gel coating is in situ synthesized on the surface of the zinc negative electrode. With the good mechanical toughness of the low-melting gel coating and the porous structure in the gel, it has excellent interfacial adhesion and lower interfacial impedance. It can promote the uniform deposition of zinc during the charge and discharge process, significantly inhibit the hydrogen evolution side reaction, inhibit the growth of zinc dendrites and the generation of by-products, and greatly improve the cycle stability of zinc-ion batteries.
[0021] 2. The preparation method of the low-melting gel coating is simple, easy to operate, has good repeatability, short time consumption, is suitable for large-scale production, and has industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022]
Figure 1
[0023]
Figure 2
[0024]
Figure 3
[0025]
Figure 4
Figure 5
[0026]
Figure 6
[0027]
Figure 7
[0028]
Figure 8
[0029]
Fig.10
[0030]
Fig.11
[0031]
Fig.12
[0032]
Fig.13
[0033] The drawings of the present invention are only used for illustrative purposes and are not to be construed as limiting the present invention.
[0034] The present invention will be described in detail below by way of examples. The following examples are intended to illustrate the present invention rather than to further limit the scope of protection of the present invention. In the following examples, unless otherwise specified, all raw materials used are commercially available.
[0035] Example 1
[0036] A polymerizable deep eutectic solvent composed of zinc tetrafluoroborate, acrylamide and glycerol
[0037] Weigh 4 g of acrylamide (AAm), 1.2956 g of glycerol (Gly) and 6.7248 g of zinc tetrafluoroborate (ZTH), mix them in a reaction reagent bottle, and then stir at 60°C for 0.5 h to form a clear polymerizable low eutectic solvent. The appearance of the polymerizable low eutectic solvent sample is as follows: Figure 1 shown.
[0038] Example 2
[0039] This embodiment provides a low eutectic gel based on a polymerizable low eutectic solvent, comprising
[0040] Glycerol 0.6478 g;
[0041] Acrylamide 2.0g;
[0042] Zinc tetrafluoroborate 3.3624 g;
[0043] Photoinitiator 2-oxoglutaric acid 0.0123 g;
[0044] And prepared as follows:
[0045] S1: Weigh acrylamide, glycerol and zinc tetrafluoroborate in a container, heat and stir at 60° C. until a clear and transparent liquid is obtained, thereby completing the preparation of a polymerizable low eutectic solvent.
[0046] S2: preparing a prepolymer solution: weighing an initiator, adding it to the polymerizable low eutectic solvent prepared in step S1 and mixing evenly.
[0047] S3: Place the solution prepared in S2 in a mold and cure it by UV. The UV light source power is 30W and the irradiation time is 20min. Add it into the silicone dumbbell mold and then irradiate it with UV light to obtain a dumbbell-shaped low eutectic gel sample (gel sample code PAZG 0.5 , wherein PA refers to polyacrylamide, Z refers to zinc salt, G refers to glycerol, and the number 0.5 refers to the molar ratio of glycerol to zinc salt).
[0048] In this example, two other types of gels were prepared as control groups. The first control group was a hydrogel of polyacrylamide (PA). The raw materials of the PA hydrogel were acrylamide (2.0 g) and water (3.3624 g). Acrylamide was dissolved in water, and 0.0123 g of a photoinitiator, 2-oxoglutaric acid, was introduced. The remaining steps were the same as those of the PAZG hydrogel described above. 0.5 similar.
[0049] The second control group was polyacrylamide hydrogel (PAG) containing glycerol. The raw materials of PAG hydrogel were acrylamide (2.0 g), glycerol (0.6478 g) and water (3.3624 g). The rest of the steps were the same as those of PAZG hydrogel. 0.5 similar.
[0050] The mechanical tensile properties test results of the three types of gels are shown in Figure 2 The tensile rate was 50 mm / min. The results showed that the eutectic gel (PAZG 0.5 ) has the largest fracture stress (0.748MPa) and fracture strain (1246%).
[0051] Example 3
[0052] Example 3 was carried out using the same process as Example 2, except that in Example 3, the solution prepared in S2 was injected into a 2 mm thick square silicone mold with zinc foil as the substrate, and then covered with glass. The mold was then cured by ultraviolet light (the power of the ultraviolet light source was 30 W, and the irradiation time was 20 min) to obtain a low eutectic gel adhered between the zinc foil and the glass. Figure 3 The adhesion performance of the three types of gels to glass substrates and zinc foil substrates is shown. 0.5The adhesion strength to zinc foil is the highest, reaching 1.21 MPa, indicating that the introduction of zinc salt promotes the adhesion between the gel and zinc foil.
[0053] Example 4
[0054] Preparation of zinc foil anode modified with eutectic gel coating using polymerizable eutectic solvent composed of zinc tetrafluoroborate, acrylamide and glycerol
[0055] Weigh zinc tetrafluoroborate, acrylamide and glycerol in a reaction container, stir at 60°C for 0.5h to form a polymerizable low eutectic solvent, and then introduce a photoinitiator. Coat them on zinc foil, press them with a mold, and then cure them with ultraviolet light (irradiation time is 1h) to obtain a zinc foil negative electrode modified with a low eutectic gel coating (named Zn@PAZG 0.5 ). Unmodified bare zinc foil was used as a control and the contact angle test was performed on it (the electrolyte was 2M ZnSO4). Figure 4 For bare zinc and Zn@PAZG 0.5 The contact angle picture of Zn@PAZG. The experimental results show that 2M ZnSO4 solution 0.5 The contact angle of the zinc anode is 55.1°, which is smaller than the contact angle of the bare zinc anode (102.3°), indicating that the 2MZnSO4 electrolyte and Zn@PAZG 0.5 The negative electrode interface compatibility is better.
[0056] Example 5
[0057] Preparation of zinc foil anode modified with eutectic gel coating by polymerizable eutectic solvent composed of different monomers and zinc tetrafluoroborate
[0058] Zinc tetrafluoroborate, monomers and glycerol are weighed, wherein the monomers are acrylamide (AAm), N-isopropylacrylamide (NIPAM) and N,N-dimethylacrylamide (DMA), respectively, and then mixed in a reaction container, and stirred at 60°C for 0.5h to prepare a polymerizable low eutectic solvent. Then, a photoinitiator is introduced into the polymerizable low eutectic solvent, which is coated on zinc foil, and then cured by ultraviolet light (irradiation time is 1h) to obtain a zinc foil negative electrode modified with a variety of low eutectic gel coatings.
[0059] Asymmetric cells were assembled using stainless steel foil (SS) and zinc foil negative electrode modified with low eutectic gel coating, and the electrolyte was 2M ZnSO4. Linear sweep voltammetry (LSV) tests were performed using an electrochemical workstation. The test results are shown in Figure 5 . Figure 5The LSV curves of Zn / / SS asymmetric cells assembled with zinc foil modified with eutectic gel coatings synthesized with different monomers are shown. When the monomer is a zinc foil negative electrode modified with a eutectic gel coating synthesized with N-isopropylacrylamide (NIPAM), the assembled Zn / / SS asymmetric cell exhibits a more negative hydrogen evolution potential (-145mV). The hydrogen evolution potential of the Zn / / SS asymmetric cell assembled with bare zinc is -76mV. The hydrogen evolution potential is mainly related to the electrochemical activity of water molecules. The results show that the activity of the hydrogen evolution reaction (HER) in the battery assembled with a zinc foil negative electrode modified with a eutectic gel coating is suppressed, which helps to improve the cyclic reversibility of zinc.
[0060] Example 6
[0061] Zinc foil anode modified by eutectic gel coating composed of zinc acetate, N-isopropylacrylamide and glycerol
[0062] Weigh N-isopropylacrylamide, glycerol and zinc acetate in a reaction container, and stir at 60°C for 0.5h to form a polymerizable low eutectic solvent. Introduce a photoinitiator into the low eutectic solvent, coat it on zinc foil, and then cure it with ultraviolet light (irradiation time is 1h) to obtain a zinc foil negative electrode modified with a low eutectic gel coating containing zinc acetate.
[0063] Asymmetric cells were assembled using stainless steel foil (SS) and coated zinc foil, and the electrolyte was 2M ZnSO4. LSV tests were performed using an electrochemical workstation. The test results are shown in Figure 6 .
[0064] Figure 6 The LSV curve of the Zn / / SS asymmetric battery assembled with a zinc foil negative electrode modified by a low-melting gel coating synthesized by zinc acetate, N-isopropylacrylamide and glycerol is shown, and the hydrogen evolution potential is -126mV. The hydrogen evolution potential of the Zn / / SS asymmetric battery assembled with bare zinc is -76mV.
[0065] Example 7
[0066] Zinc foil anode modified by eutectic gel coating composed of other alcohols
[0067] Example 7 uses the same method as Example 4 to prepare a zinc foil negative electrode modified with a low eutectic gel coating composed of other alcohols, except that glycerol is replaced with ethylene glycol or methanol. Figure 7The LSV curves of the Zn / / SS asymmetric battery assembled with zinc foil negative electrode modified by low eutectic gel coatings synthesized by different alcohols, acrylamide and zinc tetrafluoroborate are shown. The hydrogen evolution potential of the Zn / / SS asymmetric battery assembled with the zinc foil negative electrode modified by the coating of ethylene glycol as alcohol is -99mV, while the hydrogen evolution potential of the Zn / / SS asymmetric battery assembled with the zinc foil negative electrode modified by the coating of methanol as alcohol is -85mV. The hydrogen evolution potential of the Zn / / SS asymmetric battery assembled with bare zinc is -76mV.
[0068] Example 8
[0069] Preparation of Zn@PAZG by the method of Example 4 0.5 Negative electrode. It consists of two coated zinc foil negative electrodes (Zn@PAZG 0.5 ) assemble a Zn / / Zn symmetric battery, the electrolyte is 2M ZnSO4. In this example, a binary hydrogen bond network eutectic gel composed of acrylamide / zinc tetrafluoroborate is also prepared as a control group.
[0070] The test was carried out using a charge and discharge instrument and an electrochemical workstation. The test results are shown in Figure 8 and Fig. 9 as well as Fig.10 .
[0071] Figure 8 It shows that based on Zn@PAZG 0.5 Cycling performance of the assembled Zn / / Zn symmetric battery. -2 The cycle life under the condition of 1400h can reach. Under the same current density, the Zn / / Zn symmetric battery assembled by bare zinc can only cycle for 600h. The results show that the introduction of the coating is beneficial to the zinc deposition of the Zn / / Zn symmetric battery.
[0072] Fig. 9 The XRD data of the Zn / / Zn symmetric battery after 100 h of cycling are shown. Compared with the original Zn foil, the Zn@PAZG 0.5 The XRD spectrum of the zinc negative electrode of the assembled Zn / / Zn symmetric battery showed no obvious impurity peaks. In contrast, the XRD spectrum of the zinc negative electrode based on the uncoated Zn / / Zn symmetric battery showed a peak corresponding to Zn4(OH)6SO4·4H2O. 0.5 It has the effect of inhibiting side reactions, thus achieving a longer cycle life.
[0073] Fig.10 It shows that Zn@PAZG 0.5The interface impedance of the assembled Zn / / Zn symmetric battery. The experimental results show that the interface impedance of the Zn / / Zn symmetric battery assembled with bare zinc is 3051Ω, the interface impedance of the Zn / / Zn symmetric battery assembled with the zinc foil negative electrode modified by coating PAZ is 2109Ω, and the interface impedance of the Zn / / Zn symmetric battery assembled with the PAZG modified by glycerol is 2109Ω. 0.5 The interfacial impedance of the Zn / / Zn symmetric battery assembled with the zinc foil negative electrode modified by the coating is 794Ω. The results show that the introduction of glycerol changes the binary hydrogen bond network composed of acrylamide and zinc tetrafluoroborate, significantly reduces the interfacial impedance, and the coating and the electrolyte are in close contact, with good interfacial compatibility, forming a zinc-philic interfacial layer.
[0074] Example 9
[0075] Preparation of Zn@PAZG by the method of Example 4 0.5 Negative electrode. A Zn / / Cu asymmetric cell was assembled using zinc foil with a low eutectic gel coating, and the electrolyte was 2M ZnSO4. The electrochemical test results are shown in Fig.11 .
[0076] Fig.11 Shown Zn@PAZG 0.5 / / Coulombic efficiency of Cu asymmetric cell and Zn / / Cu asymmetric cell. At a current density of 1 mA cm -2 Next, Zn@PAZG 0.5 / / Cu asymmetric battery can cycle 1400 times. However, the Zn / / Cu asymmetric battery assembled with bare zinc can cycle only 700 times, and the coulombic efficiency is significantly reduced. The experimental results show that the PAZG coating 0.5 It promotes the stability of the zinc negative electrode, and the coating has obvious advantages in the cycle stability of zinc ion deposition.
[0077] Example 10
[0078] Preparation of Zn@PAZG by the method of Example 4 0.5 The negative electrode is manganese dioxide doped with carbon nanotubes (MnO2@CNTs) as the positive electrode, Zn@PAZG 0.5 Assembling Zn@PAZG for negative electrode 0.5 / / MnO2@CNTs battery, the electrolyte is 2M ZnSO4 and 0.5MMnSO4. The full battery cycle performance test and electrochemical test were carried out on it. The test results are shown in Fig.12 and Fig.13 .
[0079] Fig.12 Shown Zn@PAZG 0.5 / / Cyclic voltammetry (CV) curves of MnO2@CNTs and Zn / / MnO2@CNTs batteries. At a scan rate of 0.1 mV s-1 CV curves of the full cell. Zn / / MnO2@CNTs and Zn@PAZG 0.5 / / The CV curves of MnO2@CNTs show two pairs of oxidation and reduction peaks, corresponding to the proton and Zn 2+ Insertion / extraction of ions. Fig.13 Shown Zn@PAZG 0.5 / / MnO2@CNTs and Zn / / MnO2@CNTs battery cycling performance. Zn@PAZG 0.5 / / MnO2@CNTs battery at 1A -1 The capacity retention rate of the Zn / / MnO2@CNTs battery is close to 90% after 2500 cycles at a current density of , while the capacity retention rate of the Zn / / MnO2@CNTs battery drops to 25% after 1000 cycles under the same conditions.
Claims
1. A zinc foil negative electrode modified with a low eutectic gel coating, characterized in that: A low eutectic gel coating is in situ synthesized on the surface of zinc foil, wherein the low eutectic gel coating is obtained by polymerizing a polymerizable low eutectic solvent composed of a metal zinc salt hydrogen bond acceptor, an acrylamide monomer and an alcohol hydrogen bond donor.
2. The polymerizable deep eutectic solvent according to claim 1, characterized in that The preparation raw materials include hydrogen bond donors and hydrogen bond acceptors, wherein the hydrogen bond donors are unsaturated double bond acrylamide monomers and alcohols, and the hydrogen bond acceptors are metal zinc salts.
3. The polymerizable deep eutectic solvent according to claim 2, characterized in that The acrylamide monomer is one or more of acrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide.
4. The polymerizable deep eutectic solvent according to claim 2, characterized in that The alcohol includes one or more of monohydric alcohol and polyhydric alcohol.
5. The polymerizable deep eutectic solvent according to claim 2, characterized in that The metal zinc salt is one or more of zinc tetrafluoroborate, zinc acetate and zinc chloride.
6. The polymerizable deep eutectic solvent according to any one of claims 1 to 5, characterized in that The molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 0.1:1 to 10:
1.
7. A method for preparing a zinc foil negative electrode modified with a low eutectic gel coating, characterized in that: The steps include: S1: mixing the hydrogen bond acceptor and the hydrogen bond donor in a certain molar ratio, heating and stirring until the mixture becomes clear and transparent, thereby obtaining a polymerizable low eutectic solvent; S2: adding a small amount of initiator to the solution prepared in step S1 and mixing evenly to obtain a prepolymer solution; S3: The prepolymer solution obtained in S2 is coated on a metal zinc foil, and then polymerized under light conditions to obtain a low eutectic gel coating.
8. The method for preparing a zinc foil negative electrode modified with a eutectic gel coating according to claim 7, characterized in that: The initiator is a photoinitiator, and the photoinitiator includes one or more of 2-oxoglutaric acid, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
9. The use of the zinc foil negative electrode modified with the low eutectic gel coating according to claim 1, characterized in that: Used to prepare zinc ion batteries and zinc metal energy storage devices.
Citation Information
Cited By
Aqueous zinc ion battery and preparation and application of modified zinc negative electrode of aqueous zinc ion battery
CN119833526A
Preparation and application of aqueous zinc-ion battery and modified zinc anode thereof
CN119833526B